PENYULUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA KAMAR OPERASI DI RSU SEMBIRING TAHUN 2023 - siddiq, muhraza; Perangin-angin, Guntur; Sholikh, Akhmad Fathikus (INSTITUT KESEHATAN DELI HUSADA, 2024)
Personal Protective Equipment (PPE) is a tool that has the ability to protect someone on the job that serves to isolate workers from hazards in the workplace. Effective PPE must be used appropriately and in accordance with the risks faced. The selection of PPE, especially for nursing personnel, must be based on the risk or danger when carrying out nursing activities. PPE for health workers when practicing consists of gloves, masks, headgear, protective gowns, aprons, glasses, shoes. The purpose is determine the level of discipline the surgical team in the use of personal protective equipment in the emergency room of Sembiring Hospital, Delitua This research design is descriptive. The population in this study were all surgical teams that had been averaged with a total of 24 respondents, with consecutive sampling technique. Data was collected by observation method. It was found that of the 24 surgical team respondents, most of the undisciplined respondents were 16 people (67%) and a small number of disciplined respondents were 8 people (33%) The PPE that was most often not used by the surgical team was in personal protective equipment (googgles), namely 16 people (67%). The level of discipline of the surgical team in the use of PPE was found to be mostly undisciplined respondents and a small proportion of disciplined respondents.